2010
DOI: 10.1007/s13280-010-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Services Provided from Riparian Forests in the Nordic Countries

Abstract: Riparian forests (RF) growing along streams, rivers and lakes comprise more than 2% of the forest area in the Nordic countries (considering a 10 m wide zone from the water body). They have special ecological functions in the landscape. They receive water and nutrients from the upslope areas, are important habitats for biodiversity, have large soil carbon stores, but may emit more greenhouse gases (GHG) than the uplands. In this article, we present a review of the environmental services related to water protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 59 publications
1
52
0
1
Order By: Relevance
“…In addition to above-mentioned factors, the location of clear-cut area in relation to the stream may cause variability in treatment effects among studies (Kreutzweiser et al 2008;Abdelnour et al 2011). Also the properties of buffer zones may affect responses (Gundersen et al 2010). The efficiency of buffer zones to reduce nutrient export depends on soil and topographical characteristics of buffer zone, hydrological pathways, vegetation and microbial activity and dimensions of buffer zones in relation to the upslope area (Gundersen et al 2010).…”
Section: Specific Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to above-mentioned factors, the location of clear-cut area in relation to the stream may cause variability in treatment effects among studies (Kreutzweiser et al 2008;Abdelnour et al 2011). Also the properties of buffer zones may affect responses (Gundersen et al 2010). The efficiency of buffer zones to reduce nutrient export depends on soil and topographical characteristics of buffer zone, hydrological pathways, vegetation and microbial activity and dimensions of buffer zones in relation to the upslope area (Gundersen et al 2010).…”
Section: Specific Concentrationsmentioning
confidence: 99%
“…Also the properties of buffer zones may affect responses (Gundersen et al 2010). The efficiency of buffer zones to reduce nutrient export depends on soil and topographical characteristics of buffer zone, hydrological pathways, vegetation and microbial activity and dimensions of buffer zones in relation to the upslope area (Gundersen et al 2010). The number of catchment pairs in the present study is not sufficient to fully analyze and explain observed variation, and further studies are needed to clarify the role of catchment characteristics in different responses to clear-cutting.…”
Section: Specific Concentrationsmentioning
confidence: 99%
“…A study (literature review) on environmental services provided from Riparian Forests (RF) in the Nordic countries was also presented (Gundersen et al 2010). RF's have special ecological functions in the landscape such as buffering the impacts from upland management (protecting water bodies from nutrients released) and they are important for biodiversity.…”
Section: Ecosystem Services In Forests -Research and Research Needsmentioning
confidence: 99%
“…Finally, to what degree are these land-water linkages buffered by riparian vegetation and organic soils? Indeed, refining our understanding of the role of riparian zones seems particularly important [103]. There is evidence that certain aspects of water quality may be maintained by riparian processes, which can include the retention of nutrients and sediments from upslope terrestrial habitats [104].…”
Section: Future Research Needsmentioning
confidence: 99%